Theories of Economic Fluctuations and their Influence on the Formation of the Modern Paradigm of Economic Activity of Enterprises - Kashchena, N. (Економічний вісник Донбасу, 2020)
The article is devoted to the substantiation of the influence of the theory of economic fluctuations on the economic activity of enterprises. The influence of economic fluctuations at the macrolevel of the economy on economic activity at the microlevel of business entities is noted. A systematic approach to determining the economic activity of the enterprise as a phenomenon with a complex internal structure is analyzed in detail. Peculiarities of determining the effect of systematization in the interaction of components of business activity of the enterprise are analyzed: economic, managerial, financial, innovative, investment, marketing, labor, production. Attention is focused on the main goal in the management of the business activity of the enterprise as the formation of all types of activity at the exit from the system – it can be achieved by purposefully ensuring the activity of the enterprise both at the entrance to the system and in the process of transformation. The phases of formation of economic activity of the enterprise according to the theory of economic fluctuations are separated: formation; growth; maximum value; reduction. It is proved that at each phase of the business cycle the economic behavior of the enterprise changes. The urgency of measures to assess economic activity in the system of assessing the overall business activity of economic entities has been stated. The internal and external factors influencing the change of economic activity of the enterprise are defined. The importance of assessing the activity of the enterprise in the management system of economic activity as a system of "entrance-exit" of the relevant indicators is considered. The formation of control and managed subsystems in the mechanism of management of economic activity of enterprises in market conditions is analyzed. The main result of the study is the development of a management system of economic activity as a component of business activity of enterprises. Effective recommendations to ensure a high level of economic activity of enterprises in an unstable market environment are provided.